Self-reported hearing loss is associated with poorer perceived health care access, timeliness, satisfaction, and quality: Findings from the Survey of the Health of Wisconsin. Issue 1 (January 2023) - Dillard, Lauren K.; Nelson-Bakkum, Erin R.; Walsh, Matthew C.; Schultz, Amy
Abstract: Background: Hearing loss is a highly prevalent chronic condition impacting communication and may negatively influence patients' health care experiences. Objective: Determine associations of hearing loss with perceived health care access, timeliness, satisfaction, and quality in a representative sample of the general population. Methods: The Survey of the Health of Wisconsin (SHOW) is a household-based examination survey that collects data from a representative sample of Wisconsin residents. SHOW participants from years 2008–2013 with data on self-reported hearing loss and health care access, timeliness, satisfaction, and quality were included in this study. Age- and sex- and multivariable-adjusted (additionally adjusted for race/ethnicity, education, marital status, public health region, smoking, chronic disease, self-reported health, and insurance coverage) logistic regression models were used to evaluate associations of hearing loss with participants' health care experiences. Results are presented as odds ratios (OR) with corresponding 95% confidence intervals. Results: There were 2438 individuals (42.1% men) included in this study with an average age of 48.3 (range 21–74; standard deviation [SD] 14.4) years. The number of participants who self-reported hearing loss was 642 (26.3%). After multivariable adjustment, hearing loss was associated with increased odds of perceived difficulties with health care access (OR 1.47 [1.05, 2.05]), timeliness (OR 1.69 [1.23, 2.32]), quality (OR 2.54 [1.50, 4.32]), and satisfaction (OR 2.50 [1.51, 4.13]). Conclusions: Given the high prevalence of hearing loss and the growing aging population, there is an urgent need to prioritize interventions to improve health care provision for individuals with hearing loss.